Women’s decision-making power and knowledge of prevention of mother to child transmission of HIV in sub-Saharan Africa - Zegeye, Betregiorgis; Ahinkorah, Bright O.; Ameyaw, Edward K.; Seidu, Abdul-Aziz; Olorunsaiye, Comfort Z.; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Sub-Saharan Africa (SSA) bears the highest burden of Human Immunodeficiency Virus (HIV) in the world. Even though the prevention of mother to child transmission (PMTCT) programmme is one of the strategies to control the HIV pandemic, the uptake in SSA countries is low. Women’s decision-making power has a positive influence on health seeking behavior and uptake of several maternal health services. However, its relationship with knowledge of PMTCT services is understudied in SSA. Therefore, this study aimed to examine the association between women’s decision-making power and knowledge of PMTCT in 24 countries in SSA. Methods Analysis of this study included data on 158,812 married women from the Demographic and Health Surveys of 24 sub-Saharan African countries conducted between 2010 and 2020. Using Stata version-14 software, bivariate and multivariable logistic regression analyses were conducted. The results were presented using adjusted odd ratios (aOR) with the corresponding 95% confidence intervals (CI). Results In the pooled results, 69.5% (95% CI; 66.7–72.1%) of married women in the studied countries had knowledge of PMTCT, ranging from 13.9% (95% CI; 11.9–16.2%) in Comoros to 75.4% (95% CI; 73.7–76.9%) in Zimbabwe. Higher odds of PMTCT knowledge were seen among married women who had decision-making power compared to married women who had no decision-making power. Moreover, we found higher odds of PMTCT knowledge among married women with manual occupation, those in the richest households and those with 1–2 children compared to married women who were not working, from the poorest households, and those with no children, respectively. Conclusion Women’s decision-making power had positive influence on PMTCT knowledge. To increase the coverage of PMTCT knowledge, policy makers and other stakeholders need to target ways to empower women through increasing women’s decision-making power. Moreover, creating employment opportunities and economic empowerment for women need to be considered, especially in countries with very low coverage of PMTCT knowledge.